Menstrual Cycle and Sport: effects on the performance and metabolism of the athlete woman - Nuria Giménez-Blasi; Jose Antonio Latorre; Manuel Martínez-Bebia; Marina Sáenz; Leticia Cantero; Alejandro López-Moro; Maria Jose Jimenez-Casquet; Javier Conde-Pipo; Miguel Mariscal-Arcas (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
There are difficulties planning female training. The aim of this meta-analysis work is to know results obtained in studies on the relationship between the menstrual cycle (MC), diet, metabolism and performance in sportswomen. This work began in January-2022 looking differences in performance depending on the MC phase; exclusion criteria after 2015, non-experimental articles with quality indexes >Q2. We finally worked on 11 articles. Perception of the majority of sportswomen is that MC does have an impact on sports performance, as they are affected both physically and psychologically depending on the MC phase. Participant characteristics, such as training history, may also contribute to the variety of responses observed in studies. MC phase where performance may be reduced is in the Early Follicular Phase and may improve in the other MC phases. The effects found maybe of most relevance to female athletes.